Influence of body position on the pulse and blood pressure, observations at sea level and at altitude - García Godos R., Mariano (1945)
This paper, through the study of blood pressure and heart rate in relation to postural changes, has a dual purpose: First, make a comparative study of the responses of residents sea level and the height, to thereby reach a deeper understanding of the mechanisms of circulatory adaptation of subjects living at high altitudes knowledge. Second, recent works by American authors emphasize the interest of the study of these responses in the selection of pilots, as postural changes so frequent in this profession can be taken as one of the indices (among many others) their ability to neurocirculatory adaptation more difficult to perform when the subject comes to heights. This is of particular interest when it comes to military pilots, for technical reasons, often have to perform sudden changes in position. In these cases if the neuro-circulatory response is not adequate, that is, if the vascular tone responds not properly adapting to changes occurring, the gravity acting on the blood may produce conditions plethora in the lower regions of the body, and worse yet cerebral anemia, which can be fatal in some cases. This is what is known in aviation medicine under the name of "black out" and is suffered by the pilots during the so-called dive bombing. Straightening the plane after a tailspin, the force of gravity exerted on the man and the plane is 6 or 7 times. When this force is made in man's head to the feet, blood travels to the legs and abdomen. Blood is evicted from the upper and lower zones, causing ischemia of the brain, which produces characteristic symptoms: heavy legs, amaurosis, and fainting.